Synthesis of NiS nanoparticles using a sugar-ester nonionic water-in-oil microemulsion - Khiew, P.S.; Huang, N.M.; Radiman, S.; Ahmad, M.S. (2004)
Nickel sulfide (NiS) nanoparticles were prepared in water-in-oil (w/o) microemulsion system containing sucrose ester as the surfactants. The commercial food grade sucrose monoester (abbreviated S-1170) is a biodegradable and non-toxic surfactant, which can be adopted to form w/o microemulsion system in the presence of 1-butanol as co-solvent. The pseudo-ternary phase diagram for the inverse microemulsion region has been determined by the titration method. It was found that the studied system forms clear and homogenous microemulsion when heated to 37 Â°C but gradually becomes turbid at room temperature due to the phase separation. The as-prepared NiS nanoparticles were characterized by energy filter transmission electron microscopy (EFTEM), UV-VIS-NIR absorption spectroscopy and X-ray photoelectron spectroscopy (XPS). The results showed that the synthesized nanoparticles have regular shape, monodispersed and in the size range of 3-12 nm. Â© 2003 Elsevier B.V. All rights reserved.